2017
DOI: 10.3389/fncom.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Analysis of the Function of Three Inhibitory Cell Types in Contextual Visual Processing

Abstract: Most cortical inhibitory cell types exclusively express one of three genes, parvalbumin, somatostatin and 5HT3a. We conjecture that these three inhibitory neuron types possess distinct roles in visual contextual processing based on two observations. First, they have distinctive synaptic sources and targets over different spatial extents and from different areas. Second, the visual responses of cortical neurons are affected not only by local cues, but also by visual context. We use modeling to relate structural… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 52 publications
(130 reference statements)
1
49
0
Order By: Relevance
“…Finally, since SST+ interneurons target the dendrites of excitatory neurons, it was suggested that SST+ neurons may gate the inputs onto excitatory neurons (Lee et al, 2017; Wang et al, 2004), and computational models suggest that SST+ interneurons can selectively gate inputs that originate from different areas or pathways (Yang et al, 2016). Therefore, higher SST+ interneuron density in the medial associational and lateral areas can also allow for a larger repertoire of selective neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since SST+ interneurons target the dendrites of excitatory neurons, it was suggested that SST+ neurons may gate the inputs onto excitatory neurons (Lee et al, 2017; Wang et al, 2004), and computational models suggest that SST+ interneurons can selectively gate inputs that originate from different areas or pathways (Yang et al, 2016). Therefore, higher SST+ interneuron density in the medial associational and lateral areas can also allow for a larger repertoire of selective neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been attempts to make more realistic circuit models which include subtypes of interneurons [71,72]. Lee et al (2017) were able to replicate multiple experimental findings, including function of distinct interneuron subtypes in ‘attentional gating’ as well as an explanation for differential effects of VIP/SOM activity in visual cortex [19,41].…”
Section: Future Goals For Investigation Of the Function Of Inhibitionmentioning
confidence: 99%
“…Neuronal cell types are central to brain function. The unique physiology, morphology and connectivity of different cortical interneurons and pyramidal cells shapes their functional role in local and large-scale circuit operations (Tremblay, Lee, and Rudy 2016;Lee, Koch, and Mihalas 2017;Zeng and Sanes 2017). Cell-type specific neuronal properties shape characteristic circuit oscillations associated with various computational and cognitive processes (Womelsdorf et al 2014;Veit et al 2017;Siegel, Donner, and Engel 2012) Thus, knowledge about cell types and their role in cortical circuits is key to understanding brain function.…”
Section: Introductionmentioning
confidence: 99%